T1ρ Magnetic Resonance Imaging to Assess Cartilage Damage After Primary Shoulder Dislocation. (November 2016) - Saxena, Vishal; D'Aquilla, Kevin; Marcoon, Shannon; Krishnamoorthy, Guruprasad; Gordon, Joshua A.; Carey, James L.; Borthakur, Ari; Kneeland, J. Bruce; Kelly, John D.; Reddy, Ravinder; Sennett, Brian J.
Background: Patients who suffer anterior shoulder dislocations are at higher risk of developing glenohumeral arthropathy, but little is known about the initial cartilage damage after a primary shoulder dislocation. T1ρ is a magnetic resonance imaging (MRI) technique that allows quantification of cartilage proteoglycan content and can detect physiologic changes in articular cartilage. Purpose: This study aimed to establish baseline T1ρ MRI values for glenoid and humeral head cartilage, determine whether T1ρ MRI can detect glenohumeral cartilage damage after traumatic primary shoulder dislocation, and assess for patterns in cartilage damage in anterior shoulder dislocation. Study Design: Cross-sectional study; Level of evidence, 3. Methods: Nine male patients (mean age, 32.0 years; range, 20-59 years) who sustained first-time anterior shoulder dislocations underwent 3T T1ρ MRI. Five healthy controls (mean age, 27.4 years; range, 24-30 years) without prior dislocation or glenohumeral arthritis also underwent 3T T1ρ MRI. The T1ρ relaxation constant was determined for the entire glenoid and humeral head for patients with a dislocation and for healthy controls. The glenoid and humeral head were divided into 9 zones, and T1ρ values were determined for each zone in dislocated and control shoulders to identify patterns in cartilage damage in dislocated shoulders. Results: Average overall T1ρ values for humeral head cartilage in dislocated shoulders were significantly greater than in controls (41.7 ± 3.9 ms vs 38.4 ± 0.6 ms, respectively; P = .03). However, average overall T1ρ values for glenoid cartilage were not significantly different in dislocated shoulders compared with controls (44.0 ± 3.3 ms vs 44.6 ± 2.4 ms, respectively; P = .40), suggesting worse damage to humeral head cartilage. T1ρ values in the posterior-middle humeral head were higher in patients with a dislocation compared with controls (41.5 ± 3.8 ms vs 38.2 ± 2.2 ms, respectively; P = .021) and trended toward significance in the posterior-superior and middle-superior zones (35.2 ± 4.9 ms vs 31.3 ± 1.0 ms and 33.7 ± 5.0 ms vs 30.5 ± 1.3 ms, respectively; P = .056). These 3 humeral head zones are where Hill-Sachs lesions predominate. T1ρ values in the anterior-inferior glenoid zone trended toward significance in patients with a dislocation compared with controls (47.4 ± 5.0 ms vs 43.5 ± 3.5 ms, respectively; P = .073). Conclusion: Humeral head cartilage sustained greater damage than glenoid cartilage in primary dislocation. T1ρ values were higher in glenohumeral zones associated with Bankart and Hill-Sachs lesions. Widespread initial cartilage damage may predispose patients to glenohumeral arthropathy.